MENERAPKAN MODEL “PROBLEM BASED LEARNING” PADA MATERI “GAYA DI SEKITAR KITA” DI KELAS IV SD NEGERI 1 DUKUHWALUH BANYUMAS - Intan Ayu Nur Rizki; Wakhudin (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This study aims to analyze the implementation of Problem Based Learning (PBL) in learning the material